Novel Access to Known and Unknown Thiourea Catalyst via a Multicomponent‐Reaction Approach. Issue 38 (13th October 2020) - Nickisch, Roman; Gabrielsen, Solveig M.; Meier, Michael A R.
Abstract: Thioureas are frequently used in organocatalysis and typically rely on 3, 5‐bis(trifluoromethyl) phenyl moieties motifs to enhance their catalytic activity. In this work, these common motifs were replaced with tailorable functional groups, s uch as ester or sulfone aryls, applying elemental sulfur in a multicomponent reaction (MCR) strategy for the first time for thiourea catalyst synthesis. First, several thioureas bearing aryl, benzylic or aliphatic moieties were synthesized and tested for their hydrogen bonding strength by evaluating thiourea phosphine oxide complexes via 31 P NMR and their catalytic activity in an Ugi four‐component reaction (U‐4CR). Finally, ester and sulfone aryl thioureas were tested in the aminolysis of propylene carbonate, leading to conversions similar to those previously reported in the literature using the 3, 5‐bis(trifluoromethyl)phenyl moiety, proving that these groups are suitable alternatives for the trifluoromethyl group. Abstract : Several thiourea compounds were synthesized using a multicomponent‐reaction (MCR) approach and were evaluated for their catalytic activity. p ‐(Alkylsulfonyl)phenyl and dialkylisophtalic acid ester moieties were shown to be suitable functional groups, activating thiourea catalysts in a similar magnitude as the typically used 3, 5‐bis(trifluoromethyl)phenyl groups.